Dampak Pemanfaatan Energi, Perkembangan Ekonomi, dan Wilayah Hutan terhadap emisi gas rumah kaca di AS, Rusia, Cina, dan Brasil: Impacts of Energy Utilization, Economic Development, and Forest Area on greenhouse gas emissions in the US, Russia, China, and Brazil - Muhammad Bayu Aji , Syekh; Adliawan, Ilan; Delisia Ismena Kawahyuning (JEMeS - Jurnal Ekonomi Manajemen dan Sosial, 2024)
This study examines how economic growth, the amount of forest cover, and the use of fossil fuels affect greenhouse gas emissions in four G20 countries. Employing a quantitative research method, specifically through panel data analysis, this study examines how fossil energy consumption, forest area, and economic growth affect greenhouse gas emissions. The findings reveal that fossil energy consumption significantly influences emissions, whereas forest area and economic growth exhibit an influence but without statistical significance on greenhouse gas emissions. Furthermore, the study demonstrates that both fossil energy consumption and economic growth have a negative impact on greenhouse gas emissions, implying that increased use of fossil energy in these nations leads to amplified emissions. Conversely, expanding forest areas in these four countries can reduce greenhouse gas emissions. The data used comprises cross-sectional information obtained from the World Bank and Our World in.the.period.from.2016.to.2020..The choice of.these four G20 countries for investigation stems from their significance in global economic and environmental policies.